Perancangan Aplikasi Berbasis Website untuk Mom & Baby Spa - Badariyah, Siti; Hidayat, Mohamad Alip; Fikriah, Maulida; Kasoni, Dian; Subhiyanto (Jurnal Sistem Informasi, 2025)
Abstract— In general, to get Mom and Baby Spa services, customers who will use this service must come to a relaxation place / spa / massage parlor (this is certainly troublesome for Moms & Babies because they have to leave the house) or if they want to use similar service packages available from health service providers such as hospitals or clinics and midwifery practices where mothers check their health (the cost packages offered are expensive). However, with this website, we want to create efficiency with transparent costs and customers can choose who will come to visit to provide services. This application is expected to make it easier for mothers and babies to get spa services at home without having to leave home, at an affordable cost and reach a wider market.